Modest association between health literacy and risk for peripheral vascular disease in patients with type 2 diabetes - Chiou, Shang-Jyh; Chang, Yen-Jung; Liao, Kuomeng; Chen, Chih-Dao (Frontiers in Public Health, 2022)
Objective: Health literacy plays a crucial role in managing chronic health conditions. Previous studies have revealed the positive relationship between health literacy and diabetes knowledge but few studies have focused on peripheral vascular disease (PVD) in diabetes in relation to health literacy in diabetes management. This study investigated the relationship between the risk for PVD in relation to and health literacy level with other determining factors among patients with type 2 diabetes. Method: We conducted a survey on health literacy using the Mandarin Multidimensional Health Literacy Questionnaire in the department of metabolism and endocrine systems at a regional hospital in northern Taiwan from December 2021 to May 2022 and obtained data from the hospital’s health information system (HIS) from 2013 to 2020 to identify occurrences of PVD (n=429). We performed logistic regression analysis to identify the relationship between PVD events and health literacy levels (overall and in five separate subdimensions) adjusted with other variables. Results: A longer duration of diabetes increased the risk for PVD events (P = 0.044 and 0.028). In terms of health literacy, the overall level was not significant; however, the dimension of higher levels of health literacy in acquiring health information increased the risk for PVD events (P = 0.034). Other variables were not significantly associated with the risk for PVD events. Conclusion: This study examined the risk for PVD events in terms of the duration of diabetes and provided evidence across the range of dimensions of health literacy concerning the ability to control diabetes. Those with a higher level of health literacy may be more aware of their disease situation, seek and cooperate with their healthcare providers earlier, and have more opportunities to be made aware of their health status from regular checkups than those with inadequate health literacy. These results may help providers make available more self-management tools that are adequate and sustainable for diabetes patients with poor health literacy.